Preventing Bullying with Tolerance: A Study of Islamic Law: Mencegah Bullying dengan Toleransi: Kajian Hukum Islam - Isroani, Farida; Munir, Munir (Rechtsidee, 2022)
The actualization ​​of religious tolerance is a standard of consideration consistent concept of humans towards mutual respect of other religions by living together without mixing beliefs. This research uses a qualitative case study approach through observation, interview and documentation. The supporting factor for the actualization of the value of tolerance is the goal orientation of each school member, including the principles of wholeness, unity, humanism, and socialism. While the inhibiting factors are based on experience and basic understanding related to religious differences which are influenced by: (1) character and personality, (2) psychological development, (3) parenting pattern, (4) lack of religious teaching, (5) the surrounding environment and culture, and (6) previously established social relations.